On crystal versus fiber formation in dipeptide hydrogelator systems - Houton, Kelly A (Langmuir : the ACS journal of surfaces and colloids, 2012)
Naphthalene dipeptides have been shown to be useful low-molecular-weight gelators. Here we have used a library to explore the relationship between the dipeptide sequence and the hydrogelation efficiency. A number of the naphthalene dipeptides are crystallizable from water, enabling us to investigate the comparison between the gel/fiber phase and the crystal phase. We succeeded in crystallizing one example directly from the gel phase. Using X-ray crystallography, molecular modeling, and X-ray fiber diffraction, we show that the molecular packing of this crystal structure differs from the structure of the gel/fiber phase. Although the crystal structures may provide important insights into stabilizing interactions, our analysis indicates a rearrangement of structural packing within the fibers. These observations are consistent with the fibrillar interactions and interatomic separations promoting 1D assembly whereas in the crystals the peptides are aligned along multiple axes, allowing 3D growth. This observation has an impact on the use of crystal structures to determine supramolecular synthons for gelators